Mothers as educators: the empowerment of rural Muslim women in Israel and their role in advancing the literacy development of their children - Schaedel, Bruria (International Journal about Parents in Education, 2023)
In 2003-2005, the authors implemented Success for All (SFA)-ALASH, an innovative pedagogical program to facilitate students' advancement in literacy, and School Family Partnership program (SFP) among first and second graders in two neighboring, rural, and low-SES Arab villages. The teachers implemented SFA-ALASH, combining bi-weekly workshops for the mothers to enhance their role as facilitators of literacy at home, according to Epstein's six-folded model (1995, 2001, 2006). Mothers' perceptions in creating a home environment which inspires their children to become successful learners in the school were evaluated using: 1. Participant observations of SFP activities 2. Semi-structured interviews with 47 SFP mothers. The teacher's evaluation of each child's academic performance in reading, writing and math as well as the mothers' familiarity and her participation in the programs. Findings indicate that the SFA-ALASH programs elevated the student's achievements. The teachers' evaluations of their students' academic achievements correspond with the mothers' involvement in the SFP and their active academic and social interactions with their children at home. The paper will discuss the cultural and social empowerment and transformations of the rural lower SES Muslim women via school partnership.